Liver regeneration and ethanol detoxification: A new link in YAP regulation of ALDH1A1 during alcohol‐related hepatocyte damage. Issue 4 (26th February 2022) - Zhou, Junmei; Sun, Chunbao; Yang, Lu; Wang, Jinhui; Jn‐Simon, Natacha; Zhou, Chen; Bryant, Andrew; Cao, Qi; Li, Chenglong; Petersen, Bryon; Pi, Liya
Abstract: Yes‐associated protein (YAP), a central effector in the Hippo pathway, is involved in the regulation of organ size, stem cell self‐renewal, and tissue regeneration. In this study, we observed YAP activation in patients with alcoholic steatosis, hepatitis, and cirrhosis. Accumulation of this protein in the nucleus was also observed in murine livers that were damaged after chronic‐plus‐single binge or moderate ethanol ingestion combined with carbon tetrachloride intoxication (ethanol/CCl4 ). To understand the role of this transcriptional coactivator in alcohol‐related liver injury, we knocked out the Yap1  gene in hepatocytes of floxed homozygotes through adeno‐associated virus (AAV8)‐mediated deletion utilizing Cre recombinase. Yap1  hepatocyte‐specific knockouts (KO) exhibited hemorrhage, massive hepatic necrosis, enhanced oxidative stress, elevated hypoxia, and extensive infiltration of CD11b + inflammatory cells into hepatic microenvironments rich for connective tissue growth factor (Ctgf) during ethanol/CCl4 ‐induced liver damage. Analysis of whole‐genome transcriptomics indicated upregulation of genes involved in hypoxia and extracellular matrix (ECM) remodeling, whereas genes related to hepatocyte proliferation, progenitor cell activation, and ethanol detoxification were downregulated in the damaged livers of Yap1  KO. Acetaldehyde dehydrogenase (Aldh)1a1, a gene that encodes a detoxification enzyme for aldehyde substrates, was identified as a potential YAP target because this gene could be transcriptionally activated by a hyperactive YAP mutant. The ectopic expression of the human ALDH1A1  gene caused increase in hepatocyte proliferation and decrease in hepatic necrosis, oxidative stress, ECM remodeling, and inflammation during ethanol/CCl4 ‐induced liver damage. Taken together, these observations indicated that YAP was crucial for liver repair during alcohol‐associated injury. Its regulation of ALDH1A1 represents a new link in liver regeneration and detoxification.